Faithful representations of crossed products by actions of $\boldsymbol N^k$ - Larsen, N. S.; Raeburn, Iain (MATHEMATICA SCANDINAVICA, 2001)
We study a family of semigroup crossed products arising from actions of $\boldsymbol N^k$ by endomorphisms of groups. These include the Hecke algebra arising in the Bost-Connes analysis of phase transitions in number theory, and other Hecke algebras considered by Brenken. Our main theorem is a characterisation of the faithful representations of these crossed products, and generalises a similar theorem for the Bost-Connes algebra due to Laca and Raeburn.